Foundations of real world economics : what every economics student needs to know - Komlos, John, 1944- (New York, NY : Routledge, 2019)
The 2008 financial crisis, the rise of Trumpism and the other populist movements which have followed in their wake have grown out of the frustrations of those hurt by the economic policies advocated by conventional economists for generations. Despite this, textbooks continue to praise conventional policies such as deregulation and hyperglobalization. This textbook demonstrates how misleading it can be to apply oversimplified models of perfect competition to the real-world. The math works well on college blackboards but not so well on the Main Streets of America. This volume explores the realities of oligopolies, the real impact of the minimum wage, the double-edged sword of free trade, and other ways in which powerful institutions cause distortions in the mainstream models. Bringing together the work of key scholars, such as Kahneman, Minsky, and Schumpeter, this book demonstrates how we should take into account the inefficiencies that arise due to asymmetric information, mental biases, unequal distribution of wealth and power, and the manipulation of demand. This textbook offers students a valuable introductory text with insights into the workings of real markets not just imaginary ones formulated by blackboard economists. A must-have for students studying the principles of economics as well as micro- and macroeconomics, this textbook redresses the existing imbalance in economic teaching. Instead of clinging to an ideology that only enriched the 1%, Komlos sketches the outline of a Capitalism with a human face, an economy in which people live contented lives with dignity instead of focusing on GNP.
Welcome to real-world economics -- Markets are neither omniscient nor omnipotent -- The nature of demand -- Homo oeconomicus is extinct : the foundations of behavioral economics -- Taste makers and consumption -- Firms and imperfect competition -- Returns to the factors of production -- The case for oversight, regulation, and control of markets -- Microeconomic applications on and off the blackboard -- What is macroeconomics? -- Macroeconomics part II -- Macroeconomics part III -- International trade : open economy macroeconomics -- The financial crisis of 2008 -- Conclusion: the foundations of real world economics -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Economics; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economics / Macroeconomics; BUSINESS & ECONOMICS / Economics / Microeconomics